Pomegranate Peel Extract Reduces Cisplatin-Induced Toxicity and Oxidative Stress in Primary Neuron Culture - ÇINAR, İrfan; YAYLA, Muhammed; DEMİRBAĞ, Çağlar; BİNNETOĞLU, Damla (Marmara University, 2021)
Objective: Cancer is the most common cause of death after cardiovascular diseases. Cisplatin used in most types of cancer produces neurotoxicity. In this study, we aimed to investigate the effects of pomegranate peel extract (1) in different doses, as potent antioxidants, on the prevention of neurotoxicity due to cisplatin, which is frequently used in cancer treatment. Methods: In our study, newborn rat cortex was used. 2 hours following the application of PPE at 200, 300 and 400 mg/mL, neurotoxicity was established by applying cisplatin in 50 and 100 µM concentrations. Results: In our study, cisplatin decreased cell viability in increasing doses, while PPE showed the best neuroprotective effect in high doses. Increased total oxidant capacity due to toxicity was significantly improved by PPE4. The antioxidant capacity decreased in the toxicity group showed improvement with the administration of PPE4. At the same time, increased TNF-α mRNA expression after cisplatin administration was significantly reduced with the administration of PPE4. The increased caspase 3 (CAS 3) and caspase 9 (CAS 9) mRNA expression due to cisplatin showed improvement with the administration of PPE4. Conclusion: These results indicated that PPE could inhibit cisplatin-induced neurotoxicity, and these effects may be related to anti-apoptotic and antioxidants activities.
Keywords: Primary Neuron; Sağlık Kurumları Yönetimi; Pomegranate; In-Vitro; Health Care Administration; Neurotoxicity; Pomegranate; Antioxidant; Cisplatin; Neurotoxicity; Primary neuron; Nf-Kappa-B; Antioxidant; Cisplatin; 3. Good health